Debt To Equity Ratio Terhadap Price Book Value Dengan Return On Equity Sebagai Variabel Pemediasi - Satriani, Reni; Hasbiyadi, Hasbiyadi; Sjahruddin, Herman (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study was conducted to examine the effect of return on equity ratio (ROE) in mediating the effect of debt to equity ratio (DER) on price book value (PBV) of coal sector issuers listed on the Indonesia Stock Exchange. This research is quantitative based and uses secondary data. The population of this study were 43 issuers, sample withdrawal using purposive sampling with the number of samples that met the criteria of 34 issuers that published complete financial reports from 2020-2022 so that the total sample used was 102 data analysis units. Panel data regression analysis was used with the help of Eviews 13. The results showed that the debt to equity ratio (DER) variable had a significant positive effect on price book value (PBV). In other tests, there is evidence that the debt to equity ratio (DER) has a significant positive effect on return on equity (ROE), besides that this research also finds that return on equity (ROE) has a positive and insignificant effect on price book value (PBV). For the mediation effect, there is evidence that return on equity (ROE) cannot mediate the effect of debt to equity ratio (DER) on price book value (PBV).